2022
DOI: 10.1136/annrheumdis-2022-eular.4180
|View full text |Cite
|
Sign up to set email alerts
|

Ab0314 multimorbidity Burden in Rheumatoid Arthritis

Abstract: BackgroundMultimorbidity in patients with rheumatoid arthritis (RA) has been described as the coexistence of two or more chronic diseases and is the most common cause of death in this population.ObjectivesTo describe the prevalence of multimorbidity and mortality trends in a well-characterized cohort of patients with RA.MethodsA retrospective cohort study of patients with RA (1987 ACR criteria) was conducted. Each patient was evaluated and followed by a rheumatologist in a single outpatient private center in B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Bentaleb et al [30] reported a prevalence of depression that varied between 2 to 62.11% and that of cancer at 2%. The frequency of dyslipidemia in patients was observed in the study by Varela et al [34] and Santos-Moreno et al [35] with respectively a prevalence of 26.7% and 45%. Harold et al [33] reported an asthma prevalence of 2.1%.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Bentaleb et al [30] reported a prevalence of depression that varied between 2 to 62.11% and that of cancer at 2%. The frequency of dyslipidemia in patients was observed in the study by Varela et al [34] and Santos-Moreno et al [35] with respectively a prevalence of 26.7% and 45%. Harold et al [33] reported an asthma prevalence of 2.1%.…”
Section: Discussionmentioning
confidence: 74%
“…The infection was reported by Harrold et al [33] and Varela et al [34] respectively 5.1% and 14.6%. The occurrence of infections in this population may also be favored by immunosuppressants frequently used in the treatment of polyarthritis; they are often pulmonary and urinary [34,40,44].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation